Medial artery calcification in peripheral artery disease - Kim, Tanner I.; Guzman, Raul J. (Frontiers in Cardiovascular Medicine, 2023)
Medial artery calcification (MAC) is a distinct, highly regulated process that is often identified in small and mid-sized arteries of the lower extremities. It is associated with advanced age, diabetes, and chronic kidney disease. MAC often occurs in conjunction with atherosclerotic occlusive disease in lower extremity arteries, and when seen together or in isolation, long-term limb outcomes are negatively affected. In patients with peripheral artery disease (PAD), the extent of MAC independently correlates with major amputation and mortality rates, and it predicts poor outcomes after endovascular interventions. It is associated with increased arterial stiffness and decreased pedal perfusion. New endovascular methods aimed at treating calcified lower-extremity lesions may improve our ability to treat patients with limb-threatening ischemia. Although recent developments have increased our understanding of the mechanisms contributing to MAC, further investigations are needed to understand the role of medial calcification in PAD, and to develop strategies aimed at improving patient outcomes.